PERAN ASPEK KEPERILAKUAN DALAM PENERAPAN AKUNTANSI KEBERLANJUTAN: DARI KESADARAN SOSIAL HINGGA IMPLEMENTASI ORGANISASI - Ambarwati Akib (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The successful implementation of sustainability accounting relies not only on organizational systems and policies but also on the underlying human behavior and organizational culture. This study analyzes the role of behavioral aspects in implementing sustainability accounting through an extensive literature review of national and international publications. The findings indicate that sustainability awareness, ethical values, managerial motivation, and an open organizational culture significantly shape the effectiveness of sustainability reporting. Moreover, external pressures—such as stakeholder expectations and regulatory frameworks including the Global Reporting Initiative (GRI) and Environmental, Social, and Governance (ESG) standards—reinforce organizational commitment to social and environmental accountability. Consequently, behavioral factors are essential in transforming sustainability accounting from a compliance-oriented activity into a value-driven managerial practice. This study contributes theoretically by offering a deeper understanding of how human behavior integrates with sustainability accounting practices to support long-term sustainable development.